Factors associated with blood pressure among female students in government schools, Northern Tehran - Khaef, Kosar (2014)
This cross-sectional study was conducted to determine the association between socio-demographic factors, dietary intakes, anthropometric status and physical activity with blood pressure among Iranian adolescent school-girls in Northern Tehran. The north part of Tehran was selected because their nutrition habit is closer to western diets and socio-economic level of the families is higher than other districts in Tehran. After listing all five educational districts which were located in north of Tehran, one of them was chosen by using simple random sampling. Then, the names of all government girls’ secondary schools in the chosen district were obtained from the education ministry. Finally, only 4 schools among all governmental schools which were located in the district gave permission for the study to be carried out. The secondary school comprises three grades. By random sampling one class was chosen from each level. The participants were selected by using random number through the list of the students that was obtained from registration office in each of the schools. A total of 306 secondary school-girls students aged between 12-14 years old who were not under any medications or intensive diets participated in this study. Weight, height, waist circumference and hip circumference as well as their blood pressure were taken. Dietary intake of the adolescents was determined using 3 days 24-hours dietary (one in the weekend and two weekdays). BMI-for-age was calculated using WHO growth standards. In addition, the participants were requested to fill a set of selfadministered questionnaire which appraised physical activity and sociodemographic information. The mean age of respondents was 12.99±0.82 years ranging from 12.0 to 14.0 years, and approximately half of them were studying at the third level of secondary school, 31.4% of respondents were studying at second level and 27.1% were studying at the first level. The mean± SD of BMI among respondents was 21.3±3.8 (kg/m2) and based on the WHO (2007) growth standards, 30.7% were obese and overweight while 3.9% were underweight. The mean± SD of SBP was 116.7± 0.55 and for DBP was 74.9± 0.36. According to guidelines of IPAQ short form more than half (58.5%) of the adolescents had moderate physical activity, while 22.2% had vigorous activity. On the other hand, the mean± SD of calorie intake, carbohydrate, protein and fat intake was 2025±565 kcal, 234.50±104.96 gram, 96.69±25.18 gram and 77.85±26.74 gram, respectively. Based on DRI 48% consume more than their dietary recommended intake of sodium. In addition while 66.4% of the 12 and 13 year olds consumed less than their recommended dietary intake of potassium, 32.6% of the 14 year olds were also deficit in their potassium intake less. Based on the JNC 7 complete report, for SBP less than half of the adolescents (19.6%) were pre-hypertensive and hypertensive however with 80.4% being normotensive. Less than one fifth of adolescents (18.3%) were in the range of pre-hypertension and hypertension. But there was significant correlation between family economics with weight (r=0.130, p<0.05) and height (r=0.141, p=0.01). The study also found significant positive association between systolic blood pressure and weight (r=0.542, p<0.01), height (r=0.365, p<0.01), BMI (r=0.480, p<0.01), waist circumference (r=0.418, p=0.000), hip circumference (r=0.273, p<0.01). Furthermore, there was strong and positive association between diastolic blood pressure and weight (r=0.297, p<0.01), height (r=0.187, p<0.01), BMI (r=0.262, p<0.01), waist circumference (r=0.296, p<0.01), hip circumference (r=0.238, p<0.01).There was also positive correlation between daily calorie intake and SBP (r=0.187, p<0.01) and also DBP (r=0.152, p=0.008). Beside there was negative relationship between protein intake and only SBP (r=-0.177, p<0.01). This study determined that association between carbohydrate intake and SBP was positive (r=0.151, p<0.01) and for DBP (r=0.159, p<0.01). Furthermore, there was positive association between SBP and daily sodium intake (r=0.158, p=0.006), however it was negative correlation with potassium intake (r=-0.206, p<0.01). Meanwhile, the relationship between DBP and sodium intake was positive and strong (r=0.147, p=0.010), although it was negative correlation with potassium intake (r=-0.138, p<0.01). In addition, there was only negative association between physical activity level and SBP (r=-0.117, p<0.05). Additionally, factors which were correlated with SBP were explained by BMI-for-age, WHR (r2=0.280), daily potassium intake (r2=0.294) and calorie intake (r2=0.305). Among these factors, BMI-for-age was the strongest factor that could explain of 21% of variation in systolic blood pressure. BMI-for-age and potassium were factors that contributed towards both SBP and DBP. According to the result the most important factor which was correlated to DBP was BMI-for-age (6%). This study reveals the importance of working with adolescents girls in school to achieve ideal BMI and good nutritional practices in order to prevent the development of others health problems caused by HBP both at this stage of their life or in later years.